Implementation of Scientific Ethics in Early Childhood Education (PAUD) Programs - Hasanah, Nurul; Aisyah, Eny Nur (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2024)
This research aims to explore the importance of ethical science in early childhood education (PAUD), with a focus on the role of ethics teachers towards themselves and students. The scientific ethics possessed by a teacher influences the way they manage interactions with students and the way they maintain professionalism in them. This research uses a qualitative approach with a case study method involving observation, interviews and document analysis as data collection techniques. The research sample consists of a number of teachers in several PAUD institutions who are expected to provide a comprehensive picture of the application of ethics in early childhood education. The research results show that teachers' ethics towards themselves include personal responsibility in maintaining integrity, quality and professionalism, such as maintaining morality, developing professional competence, and showing attitudes that can be emulated by students. Meanwhile, teacher ethics towards students has proven to be important in creating a learning environment that is safe, inclusive, and supports children's holistic development, including honesty, respect, and fair treatment of each child. This research also found that awareness and application of strong scientific ethics among teachers will have a positive impact on the quality of PAUD education, improve relationships between teachers and students, and support the achievement of better educational goals. The implication of this research is the need to increase ethics training for PAUD teachers as part of professional development, as well as the need for more attention to the formation of teacher character based on ethical knowledge, to create a quality and sustainable education system.